A Systematic Review of the Effect of Vitamin C Infusion and Vitamin E-Coated Membrane on Hemodialysis-Induced Oxidative Stress - Teresa, Malecka-Massalska; Magdalena, Wladysiuk; Andrzej, Ksiazek (IntechOpen, 2011)
None